PENGARUH WEIGHT TRAINING DENGAN SISTEM PIRAMID TERHADAP POWER OTOT TUNGKAI - Farhiah, Arum; Triansyah, Andika; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThere were still many abilities of limb muscle power of students in extracurricular activities at SMAN 9 Pontianak, the criteria of ability were not good, so the ability to kick on the foot has not shown maximum leg muscle power. The purpose of this study was to determine the effect of weight training with the pyramid system on the muscles of taekwondo extracurricular students.The method used in this study was an experiment with the form of pre experimental design. The population in this study was 33 extracurricular taekwondo students. Sampling in this study used purposive sampling technique, which amounted to 15 students as an experimental class. Data analysis techniques using t-test. Based on the results of the t-test on the experimental class, the value of tcount ? ttable was 7.74 ? 1.761, the results were accepted if the alternative hypothesis was accepted and the null hypothesis was rejected then the data is significant, whereas if the alternative hypothesis is rejected and the null hypothesis is accepted, the data is not significant. It can be seen from the results of the t-test calculation where the hypothesis is accepted and it means that there is an effect of weight training with percentage effect 11.5%. Keywords: Leg Muscle Power, Pyramid System, Weight Training, Pyramid System